KOMUNIKASI KEBIJAKAN PUBLIK DALAM PENANGGULANGAN INSES DI KECAMATAN TANJUNG TIRAM - Hasan Sazali Sazali (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
In people's lives, we find various kinds of deviations that are against social norms. One of the things that are rife is the incest behavior that is found in various regions. People think that incest is a family affair and does not need to be known by other parties. The purpose of this study was to analyze public policy communication in dealing with incest. This type of research is qualitative research. The data collection technique was carried out in three stages, namely through observation, interviews, and focus group discussions. The data analysis of the research results was carried out based on the source of the interview transcription information, scanning the material, typing in the field data, or sorting and compiling the existing data, then the data was compiled based on the information source, second, reading the entire data. Then, analyze in more detail by coding-data, considering detailed instructions that can help the coding process when analyzing the existing data. Finally, describe the data findings in a narrative form. The results of this study found that the problem with incest was the lack of the government's role in public policy communication and in providing legal protection. In addition, in public policy communication to combat incest, it is necessary to exchange information and establish a two-way communication relationship between the public and the government. In the implementation of public policies carried out, the government has not been able to touch incest victims to report the events they experienced because of fear of the lack of protection for victims